Functional diversity of phytochrome family in the control of light and gibberellin-mediated germination in Arabidopsis - Arana, María Veronica (2014)
In several species, seed germination is regulated by light in a way that restricts seedling emergence to the environmental conditions that are likely to be favourable for the success of the new individual, and therefore, this behaviour is recognized to have adaptive value. The phytochromes are one of the most relevant photoreceptors involved in light perception by plants. We explored the redundancy and diversity functions of the phytochrome family in the control of seed responsiveness to light and gibberellins (GA) by using a set of phytochrome mutants of Arabidopsis. Our data show that, in addition to the well-known role of phyB in the promotion of germination in response to high red to far-red ratios (R/FR), phyE and phyD stimulate germination at very low R/FR ratios, probably by promoting the action of phyA. Further, we show that phyC regulates negatively the seed responsiveness to light, unravelling unexpected functions for phyC in seed germination. Finally, we find that seed responsiveness to GA is mainly controlled by phyB, with phyC, phyD and phyE having relevant roles when acting in a phyB-deficient background. Our results indicate that phytochromes have multiple and complex roles during germination depending on the active photoreceptor background.